2004
DOI: 10.3727/000000004773301771
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Adipose Tissue-Derived Stromal Cells Increases Mass and Functional Capacity of Damaged Skeletal Muscle

Abstract: The regenerating skeletal muscle environment is capable of inducing uncommitted progenitors to terminally differentiate. The aim of this work was to determine whether adipose tissue-derived stromal cells were able to participate in muscle regeneration and to characterize the effect on muscle mass and functional capacities after transplantation of these cells. Adipose tissue stromal cells labeled with Adv cyto LacZ from 3-day-old primary cultures (SVF1) were autotransplanted into damaged tibialis anterior muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 28 publications
1
67
1
1
Order By: Relevance
“…(Mizuno, 2010). Local or systemic administration of AdMSCs was reported to induce repair of myocardial infarction (Cai et al, 2009), liver injury (Banas et al, 2008), hypoxia-ischemia-induced brain damage (Wei et al, 2009), allergic rhinitis (Cho et al, 2009) and muscular dystrophy (Bacou et al, 2004). One of the more interesting characteristics of MSCs is their ability to migrate to areas of tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…(Mizuno, 2010). Local or systemic administration of AdMSCs was reported to induce repair of myocardial infarction (Cai et al, 2009), liver injury (Banas et al, 2008), hypoxia-ischemia-induced brain damage (Wei et al, 2009), allergic rhinitis (Cho et al, 2009) and muscular dystrophy (Bacou et al, 2004). One of the more interesting characteristics of MSCs is their ability to migrate to areas of tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…A large population of cells isolated from the stromal vascular fraction of human adipose tissue termed processed lipoaspirate (PLA) cells possesses multilineage potential (8,9). Recent reports on PLA cells have demonstrated improvement of postnatal neovascularization (10), muscle regeneration (11), high potential to heal critical-size calvarial defects (osteogenic capacity) (12), and rescue of lethally irradiated mice (stromal capacity) (13). Adipose-derived cells also appear to possess cardiomyogenic capacity in vitro; however, the significance of this capacity remains to be proven (14).…”
mentioning
confidence: 99%
“…1 Previous studies have examined the use of drugs, cytokines, cells, and gene therapy attempted to improve muscle recovery. [2][3][4][5][6][7][8][9][10] Recently, we showed that transplantation of human peripheral blood CD133-expressing cells (CD133 + cells) inhibits fibrosis and improves muscle regeneration after skeletal muscle laceration. 11 Human blood CD133 + cells are wellsuited for clinical applications, because collecting these cells is safe, with limited ethical problems.…”
mentioning
confidence: 99%